Comparative analysis of complete chloroplast genomes of Flemingia prostrata and Flemingia macrophylla, two commonly used medicinal plants in southern China - Wei, Fan; Lin, Yang; Tang, Danfeng; Liang, Ying; Qin, Shuangshuang (Frontiers in Plant Science, 2025)
Flemingia prostrata and Flemingia macrophylla, belonging to the genus Flemingia, are ethnomedicinal plants that contain valuable medicinal and nutritional compounds. However, their medicinal materials are frequently confused in the Chinese medicinal materials market. Moreover, molecular genomic resources for this genus remain limited, which hinders phylogenetic studies. In this study, the complete chloroplast (cp) genomes of F. macrophylla and F. prostrata were sequenced to enable genome comparison and phylogenetic analysis. Both cp genomes exhibited typical quadripartite structures, with genome sizes of 152,937 bp for F. macrophylla and 153,033 bp for F. prostrata. Each genome consisted of a large single copy (LSC) region (83,594 and 83,701 bp, respectively), a small single copy (SSC) region (17,773 and 17,776 bp, respectively), and two inverted repeats (IR) regions (50,570 and 51,556 bp, respectively). A total of 129 genes were annotated in each cp genome, including 8 ribosomal RNAs, 83 protein-coding genes, and 37 transfer RNAs. Comparative analysis revealed that although the overall genome structure, codon usage bias, simple sequence repeats (SSRs), and dispersed repetitive sequences were relatively conserved between the two cp genomes, certain genomic variations were present. Specifically, 286 SNPs and 104 indels were identified, and psaJ-rps18 showed the highest variability and could serve as potential DNA barcode regions. Furthermore, phylogenetic analysis supported a close evolutionary relationship between the genus Flemingia and Cajanus. Divergence time estimation suggested that F. macrophylla and F. prostrata diverged approximately 0.26 million years ago (Mya). Finally, we successfully distinguished the two species using SSR markers. This study lays the foundation for enriching the molecular data and phylogenetic insights of this genus, as well as for the safe application of its medicinal materials.